Smart City Policy in Indonesia: An Overview from the Green Constitution's Perspective - Muhammad Kamal; Rizki Ramadani; Hardianto Djanggih (Sekolah Tinggi Hukum Bandung, 2022)
Smart city is now become an alternative policy to address various urban ecosystem’s issues. This article examines smart city policies in Indonesia, as well as the extent to which these policies can fulfill citizens' rights from the green constitution’s perspective. This is a normative/doctrinal legal research with statutory and conceptual approach. Data was gathered through library research on primary legal materials in the form of related laws and regulations, as well as secondary legal materials in the form of relevant literature. The findings show that several smart city policies are still sectoral and unsustainable. A specific legal instrument is required to regulate smart city standardization to avoid misinterpretation and obstacles in its implementation. The smart city concept is consistent with the rights enshrined in Indonesia's green constitution, but policies continue to rely on local government initiative and discretion, resulting in citizens' rights not being placed proportionally.